Accurate Sensorless Multistable Microsystem With a Single Actuator - Hussein, Hussein; Fariborzi, Hossein (Frontiers in Mechanical Engineering, 2022)
A compact and monolithic multistable microsystem was developed to realize the accurate positioning on the microscale by using a single actuator, without any positioning sensors. The mobile part can be maintained in several stable positions at rest with accurate intermediate steps and a high stability margin at each position. Switching between stable positions can be performed in both directions on one axis by using a single actuator. Using the mechanical intelligence encoded in the internal mechanisms, the mobile part position can be switched one step forward or back to the initial position through a single activation of the actuator. Multistable devices were designed and fabricated based on the working principle, and their satisfactory operation, with effective holding at stable positions and switching in two directions, was experimentally demonstrated.